Latex glove protein detection using maximum-minimum clustering variation technique - Ting, Huong Yong; Ong, Chia Sui; Sim, Kok Swee; Tso, Chih Ping (2009)
An improvement to previously proposed maximum-minimum variation (MMV) test for protein levels quantification is reported. The additional process is artefacts segmentation in latex glove sample by using k-means clustering algorithm. The new proposed maximum-minimum clustering variation (MMCV) technique, give significantly better results in terms of consistency and accuracy than existing methods.